Asia and Africa in the Colonial Period - Viacheslav Iakovlevich Belokrenitskii (Сравнительная политика, 2015)
The section examines the colonial history of Asia and Africa, as well as key periods and directions of colonization. The authors analyze the features of the colonial political systems, processes of power distribution, the relationships between colonies and metropolis. Particular attention is paid to the strengthening of Asia and Africa in the final period of colonialism, as well as the impact of the Second World War and a new system of international relations on the process of decolonization.